Payment of Marriage Assets from the Perspective of Customary Law of The Maybrat Tribe in West Papua - Yusak Jimmy Kareth; George Frans Wanma; Agustinus Luturmas (LEGAL BRIEF, 2025)
This study examines the practice of marriage property payment (dowry) within the Maybrat customary law community in Papua, focusing on its forms, procedures, and socio-legal significance. The tradition centered on the highly valued Eastern Cloth (Bo) functions not only as a cultural symbol of honor and kinship integration but also as a mechanism for wealth redistribution and social legitimacy within the clan system. Using an empirical socio-legal approach, this research explores how dowry payment practices reflect collective obligations, cultural identity, and intergenerational continuity. Data were collected through legal document analysis, customary law sources, and relevant literature. The findings show that dowry payment rituals, including the proposal (Amu Nfot Bofot), negotiation, verification, and ceremonial handover, carry deep social and symbolic meaning, particularly regarding respect for women and family alliances. However, tensions arise when these customary practices intersect with Indonesian national law, especially concerning gender equality, marriage validity, and human rights protections. While the Constitution recognizes customary communities and their traditions, the increasing economic burden and potential commodification of women pose legal and ethical challenges. The study concludes that harmonizing customary norms with national legal principles requires inclusive dialogue and adaptive legal frameworks that respect cultural identity while safeguarding fundamental rights